2007
DOI: 10.1007/s10499-007-9139-5
|View full text |Cite
|
Sign up to set email alerts
|

Growth, absorption and assimilation efficiency by mature cuttlefish (Sepia officinalis) fed with alternative and artificial diets

Abstract: The effects of feeding three natural frozen diets, grass shrimp (Palaemonetes sp.), crayfish (Procambarus clarkii) and fish (Sardina pilchardus) and two semi-humid artificial diets (based on fish powder) to mature cuttlefish, Sepia officinalis, were analysed. Growth and feeding rates (GR and FR, % BW day -1 ), food conversions (FC, %), and total protein and lipid composition of the diets were determined. Digestive gland to body weight ratio and absorption efficiency were calculated for each diet. Cuttlefish fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…In fact, increases of faeces were recorded in animals fed boiled or ovendried shrimp, showing that this type of meat was not adequately digested. Previous work on S. officinalis showed that diets made with fish meal and supplemented with sardine and squid paste produced similar results (high production of faeces and low absorption efficiency), showing that when protein sources were modified (as the fish meal) assimilation efficiency was limited (Domingues 2007a). The reason for that limited digestibility of processed protein could be related to changes in protein structure.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…In fact, increases of faeces were recorded in animals fed boiled or ovendried shrimp, showing that this type of meat was not adequately digested. Previous work on S. officinalis showed that diets made with fish meal and supplemented with sardine and squid paste produced similar results (high production of faeces and low absorption efficiency), showing that when protein sources were modified (as the fish meal) assimilation efficiency was limited (Domingues 2007a). The reason for that limited digestibility of processed protein could be related to changes in protein structure.…”
Section: Discussionmentioning
confidence: 94%
“…The reason for that limited digestibility of processed protein could be related to changes in protein structure. Although there are some unsolved questions regarding protein structure and digestibility capabilities of cephalopods, evidence suggests that processed protein such as fish surimi paste (Castro et al 1993), catfish processed paste (Domingues et al 2005) or fish meal enriched with squid paste (Domingues et al 2007a;Rosas et al 2007) limit the digested energy in cephalopods.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations